A Study of EFL students’ interpretations of cultural aspects in foreign language learning - Hernández Castro, Osiris; Samacá Bohórquez, Yolanda (Colombian Applied Linguistics Journal, 2006)
This article explores the relevance of implementing the cultural aspects of both foreign and own countries as a paramount issue in the teaching of a target language. This small scale research project was developed as a component of the seminar on Bilinguism offered by Universidad Distrital in Bogotá as part of its Master´s program in Applied Linguistics to the Teaching of English. The authors of this research collected data to find out and compare how university students from Tunja and Bogotá –two major Colombian cities– assess the incorporation of cultural aspects of the foreign country into the teaching of the foreign language. Thus, the guiding question of this research is: How do EFL students interpret cultural aspects embedded in foreign language learning?